A Comprehensive Comparison and Analysis of Several Intensity Modulations Based on the Underwater Photon-Counting Communication System - Han, Xiaotian; Li, Peng; Chang, Chang; Gao, Duorui; Zhang, Dongquan; Liao, Peixuan; Wang, Wei; Xie, Xiaoping (Frontiers in Physics, 2022)
Underwater wireless optical communication is facing absorption, scattering problems, which, in principle, can be greatly resolved by underwater photonic counting communication (UPCC) technology that exhibits high sensitivity communication characteristics in long-range underwater wireless optical communication. Recent studies on UPCC are mainly focused on a single intensity modulation like OOK and PPM technologies, and the comprehensive analysis of communication performance combing OOK modulation and digital pulse modulations remains a lack. To this, by using a UPPC system based on a single-photon avalanche diode, we reveal the communication performances of OOK, PPM, DPIM, DPPM, and DH-PIM, and find that (1) the PPM has the longest transmission distance at the same BER when M>2, but the lowest communication rate under identical modulation bandwidth and average transmit power; (2) the DPPM and DPIM perform the optimum communication performance at the fixed communication rate when M = 8. We thus conclude that the DPPM and DPIM have advantages of low modulation bandwidth and the long time slot time compared to PPM, indicating the significance of reducing the difficulty of signal synchronization and the complexity of the underwater photon-counting system accordingly.